Implementasi Metode Ward untuk Meningkatkan Kualitas Bernyanyi: Studi Kasus Anak Sekolah Minggu Kelas Tanggung Rayon Yerusalem Jemaat Martin Luther Sentani Indonesia - Cosye Meilina Sahureka; Wouter Fangohoy (Program Studi Pendidikan Musik FBS UNP, 2024)
Purpose: The Ward method makes it easier for trainers and children to improve their singing quality. The purpose of this study was to determine how to improve singing development in Sunday school children using the Ward method. Method: The method used is the Classroom Action Method (CAR) with 4 stages carried out, namely planning, implementation/action , observing, and reflecting. Results and Discussion: The results of the implementation of the Ward method in singing show that it is very good to be applied to children who do not understand well how to read notation in songs. Their enthusiasm for learning has increased significantly. In the pre-cycle, the development of recognizing notations that appeared in children was 7 children who had not developed, with a presentation of 23.3%. Children who began to develop amounted to 10, with a presentation of 33.3%. Children who developed as expected amounted to 8, with a presentation of 26.33%, and children who developed very well amounted to 5, with a presentation of 16.6%. Conclusion: It developed in cycle 1 to 0 children who had not developed, 4 children who began to develop, 10 children who developed as expected, and 16 children who developed very well. In cycle 2, children's development in understanding notation in songs increased to 7 children who experienced development as expected (23.33%) and 23 children who experienced very good development (76.66%).